BUSINESS DEVELOPMENT IN THE DIGITAL AGE - Helisia Marganaha (International Journal of Advanced Science and Computer Applications, 2024)
In today's digital era, old systems and processes must be rethought, and new technologies must be implemented to keep businesses competitive and growing. High global competition provides its own demands for business people to continue to improve product innovation by utilising existing technology to face this global challenge. Data collection techniques on business development in the digital era are conducted through online data analysis, literature studies obtained from Google Scholar, online surveys and social media monitoring to collect information on digital businesses. The use of technologies such as big data and sentiment analysis can also help in understanding the changes that occur in the digital business ecosystem. Technology and the internet have opened up new opportunities for businesses to reach a wider market, improve operational efficiency, and accelerate business growth. High global competition puts its own demands on businesses to continuously improve product innovation by utilising existing technology to face these global challenges. Businesses that succeed in the digital era are those that can adapt quickly and remain responsive to changes in the market and technology. Businesses need to adapt to technological developments and utilise them to improve business quality and expand market reach.